Evaluación de un sistema desorción - absorción para el tratamiento de agua residual en el proceso de nitruración de la empresa Aluica S.A.S. (2020)
This project aims to evaluate a desorption-absorption system for the treatment of wastewater in the nitriding process, where the operating conditions and parameters will be established complying with regulations, as well as their manufacturing costs and operational costs, passing of a scale of laboratory to scale plant by means of numerical methods and programming accompanied with direct experimentation, with their respective repeatability, in the process of nitriding. The method consists of a packed desorption tower for an air-ammonia water system, accompanied by an absorbed tower packed for an ammonia-sulfuric acid system, in order to generate ammonium sulfate as a by-product for sale, accompanied by the wastewater treatment, incurring economic savings, reinforcing environmental responsibility and benefit in industrial safety; With the appropriate protocols and electre of the planned improvements, 56.07% removal of ammonia for desorption was obtained, and reaction results by complete absorption of the residual gas with the selected absorbent, in this case sulfuric acid; as a basic dimensioning, from heuristics and results of the experiments, a height of 1,995 meters and a diameter of 0.333 meters was obtained for the desorption tower, in addition to values of 1.75 meters high with 7 plates and a diameter of 0.33 meters for the absorption system.